Suicidality and epilepsy: A systematic review and meta-analysis - Wang, Haijiao; Zhang, Yu; Tan, Ge; Chen, Deng; Fu, Yaoqi; Liu, Ling (Frontiers in Psychiatry, 2023)
Background: We aimed to evaluate the association between epilepsy and suicidality, including suicidal ideation, attempts and completed suicide. Methods: We systematically searched PubMed, Embase, Cochrane Online Library, and Clinicaltrials.gov from 1946 to June 21, 2021. and assessed the quality of the studies using the Newcastle–Ottawa Scale. We calculated the pooled OR and the crude rate for suicidal ideation, suicide attempts and completed suicide in patients with epilepsy (PWE). Results: We screened 2786 studies and included 88 articles with 1,178,401 PWE and 6,900,657 participants as controls. Search terms included epilepsy and suicide. The pooled rates of suicidal ideation, suicide attempts and completed suicide in PWE were 19.73% (95% CI: 17.00% -22.62%), 5.96% (95% CI: 4.82%- 7.20%), and 0.24% (95% CI: 0.11% - 0.42%), respectively. Compared to the control group, PWE were at a significantly higher risk of total suicidality (pooled OR, 2.60; 95%: 2.13–3.18), including suicidal ideation (pooled OR, 2.70; 95% CI, 2.21–3.30), suicide attempts (pooled OR, 2.74; 95% CI, 2.08–3.61) and completed suicide (pooled OR, 2.36, 95% CI, 1.45 – 3.83). Subgroup analyses showed significant differences in the subgroups of the measurement of suicidality. Conclusions: The rate of suicidal ideation, suicide attempts and completed suicide in PWE were about 19.73%, 5.96%, and 0.24%. And there was an increased risk of suicidality in PWE especially temporal lobe epilepsy and drug-resistant epilepsy. Clinicians need to be aware of this risk in PWE with early identification and prevention at the time of diagnosis.